Explaining low employment rates among older women in urban China - Wenchao Jin (Institute for Fiscal Studies (IFS), 2016)
In China, the employment rate among middle-aged and older urban residents is exceptionally low. For example, 27% of 55-64-year-old urban women were in work in 2013, compared to more than 50% in UK, Thailand and Philippines. This paper investigates potential explanations of this low level of employment in urban China. I document the stylized fact that a majority of individuals stop working as soon as they qualify for a public pension, which most often happens at age 50 for women. I also highlight the presence of signi cant amounts of financial and time transfers between generations. I provide descriptive evidence that transfers from children are responsive to parental incomes, and that mother's labour supply is aff ected by the expectation of transfers from her children. I then built and calibrate a life-cycle model of labour supply and saving. I fi nd that both the pension system and transfers from children have large eff ects on female labour supply. Increasing the female pension age from the status-quo to 60 would raise the employment rate of 50-59 year old women by 28 percentage points.
Keywords: 330